Gut microbiota and metabolite variations in a migraine mouse model - Wang, Dan; Liu, Xu; Shi, Suming; Ren, Tongli; Wang, Wuqing (Frontiers in Cellular and Infection Microbiology, 2024)
Migraine is a prevalent clinical disorder characterized by recurrent unilateral throbbing headache episodes accompanied by symptoms such as nausea, vomiting, photophobia, and phonophobia. Despite its common occurrence, the diagnosis, pathophysiology, and treatment of migraine remain controversial. Extensive research has implicated the gut microbiota in various central nervous system disorders, including anxiety disorders, depression, and Parkinson's disease. Some studies have also suggested that migraine may stem from disruptions to neurohormones and metabolism. This study aimed to investigate the disparities in gut microbiota and metabolites between migraine mice model and normal mice to shed light on the underlying mechanisms and potential therapeutic approaches. Distinct differences in gut microbial composition were observed between the migraine mouse model and normal mouse, indicating a potential correlation between these variations and the pathogenesis of migraine. This study provides evidence of differences in gut microbiota composition and metabolites between a migraine mouse model and normal mice, which showed that Akkermansiaceae constituted the most abundant taxon in the sham injection mouse group, while Lachnospiraceae constituted the most prevalent group in the migraine mouse model group. The associations between the abundances of Akkermansia muciniphila and Lachnospiraceae bacteria and metabolites suggested their potential roles in the pathogenesis of migraine. The altered abundance of Lachnospiraceae observed in migraine-afflicted mice and its correlations with changes in metabolites suggest that it may affect the host's health. Thus, probiotic therapy emerges as a possible treatment for migraine. Moreover, significant disparities in gut metabolites were observed between the migraine mouse model and normal mice. These alterations encompass multiple metabolic pathways, suggesting that metabolic disturbances may also contribute to the development of migraines.